4u+13=65

Simple and best practice solution for 4u+13=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4u+13=65 equation:


Simplifying
4u + 13 = 65

Reorder the terms:
13 + 4u = 65

Solving
13 + 4u = 65

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '-13' to each side of the equation.
13 + -13 + 4u = 65 + -13

Combine like terms: 13 + -13 = 0
0 + 4u = 65 + -13
4u = 65 + -13

Combine like terms: 65 + -13 = 52
4u = 52

Divide each side by '4'.
u = 13

Simplifying
u = 13

See similar equations:

| 4p-4=56 | | 9x-90=4x+55 | | A=49sqin | | 5(x-5)+5=-50 | | 6b+3=4b+5 | | 4/k=6=11 | | f(x)=6x^2+5x+3 | | 21/3x5-11= | | 1/(2sqrtx)=0.1111111111 | | -3(2x+6)-4+5x=4(x-5)+9-2x | | 3(x-3)-20=-23 | | -n-1/6=5 | | 200+3x=2+5x | | (9x+20)+(7x+x)=180 | | 5(2x+4)=70 | | 1/2x6= | | -14=a+5 | | 28=8+2n | | -8m-6=12-5m | | 7(y-3)+2(y+4)=14 | | P(-2)=-4x^3-x^2+2x | | -3m+14=4m+7 | | 11n-12n= | | -10+4x=9+12x | | 11+2p=17 | | (9x+20)+(7x+2y)=180 | | 7+3f=19 | | 5x+3-6x=8 | | m^2+10m=c | | 3(3z-1)-3(3-2z)=9 | | h=-0.05x^2+x+3 | | 13p+17q+p-6q-3p= |

Equations solver categories